The Effects of a Non-Technical Skills Training Program on Emotional Intelligence and Resilience in Undergraduate Nursing Students - Jiménez-Rodríguez, Diana; Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Arrogante, Oscar; Oropesa-Ruiz, Nieves Fátima; Gázquez-Linares, José Jesús (Healthcare (Basel), 2022)
There is a growing body of research on emotional intelligence and resilience in nursing students. However, there is little evidence of the development of these variables in intervention programs. This study aims to analyze the effects of a non-technical skills training program in emotional intelligence and resilience. Sixty students in the second year of Nursing Education from a Spanish public university completed this psychoeducational course. The pre-experimental design was longitudinal with pre- and post-intervention evaluation. The course consisted of 12 sessions of classroom education, three small-group workshops and a set of individual activities. Results in the emotional intelligence dimensions showed that Clarity (t = 3.10, p = 0.003) and Repair (t = 3.59, p < 0.001) increased significantly after participation in the program. Furthermore, the participants had a higher Resilience index when they had completed the program, with a statistically significant difference from the pre-course mean (t = 2.83, p = 0.006). This non-technical skills training program was an effective method of improving emotional intelligence and resilience in nursing students. Therefore, its use is recommended as a psychoeducational strategy for training undergraduate nursing students, as it improves their personal and professional competencies, resulting in higher-quality care.